Dynamic propulsion system simulation - Pushparaj, Kumareshwaran; Dai, Renzhi (My University, 2016)
This report describes an investigation of the dynamic behavior of a ship’s propulsion system, through modelling of the internal combustion engine, which is the main power supply unit for a ship propulsion plant, using mean value engine model. Thermodynamic and mechanical principles of a typical diesel engine are studied in detail. The model is implemented in Simulink environment. The engine model will be integrated with the whole propulsion plant model of a naval vessel. The behavior of the entire propulsion system model is simulated under di↵erent speed. Due to limitations of the availability of sufficient data in terms of specific variables, the model will not be implemented totally according to strict physical principles. Therefore, proper simplifications and approximations are adopted to circumvent such difficulties in order to achieve satisfactory accuracy of the model prediction. The results of the simulation needs to be validated by the data from sailing experiments. This project is complemented with an extension report - description/abstract of extension: The report of the project extension contains the verification of the mean value model, calibration and validation results of three main components built in the diesel engine model, the fuel pump, the exhaust gas valve and the compressor. The verification part is to check whether the performance of the model can reflect the engine dynamic behavior reasonably under steady state, acceleration and deceleration scenarios. The calibration and validation parts are to improve the output of the blocks of those three components and to investigate their accuracy. In these blocks, some parameters have to be assumed with initial values in order to allow the whole model to run. This leads to differences between the outputs of the model and the experimental data. By using an optimization algorithm, the optimum parameters can be calculated. Then the validation is carried out with these parameters. The data of the engine speed provided by Damen shipyard ranges from 800 rpm to 1800 rpm as reported in the document “Diesel Engine experimental data - DAMEN.pdf”, which are 12 groups of experimental data. However, the model developed can only function well in the range of 1000 rpm to 1600 rpm, corresponding to the ship speeds of 10 knots to 16 knots. Here only seven groups of simulated results can be generated from the model. For each time of optimization, 4 groups of data will be used for optimization, and another 3 groups of data will be used for validation.
Keywords: Maskinteknik; Farkostteknik; Transport; Mechanical Engineering; Vehicle Engineering; Transport